2011
DOI: 10.1186/1476-069x-10-15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hourly concentration of particulate matter on peak expiratory flow in hospitalized children: A panel study

Abstract: BackgroundLittle information is available on the possible association between hourly short-term air pollution and peak expiratory flow (PEF) in asthmatic children.MethodsPEF was measured twice daily, from October through December, 2000, in 17 children aged 8 to 15 years hospitalized with severe asthma. A total of 1198 PEF measurements were made at 7 a.m. and 1175 at 7 p.m. Measurements were conducted immediately prior to medication under the guidance of trained nurses. PEF changes were estimated in 10-μg/m3 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 10 publications
3
32
0
3
Order By: Relevance
“…However, Ward et al contradicted this fact in his work [8]. Yet, Yamazaki et al seems to confirm Van der Zee's thesis [16]. Nevertheless, the absence of statistically significant influence of particulate matter and CO concentration on healthy adults' PEFR, as shown in our work has been confirmed by numerous authors [17].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, Ward et al contradicted this fact in his work [8]. Yet, Yamazaki et al seems to confirm Van der Zee's thesis [16]. Nevertheless, the absence of statistically significant influence of particulate matter and CO concentration on healthy adults' PEFR, as shown in our work has been confirmed by numerous authors [17].…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, the NO 2 and PEFR associations also remained present, even when adjusted for PM 2.5 and Ox [16].…”
Section: Discussionmentioning
confidence: 89%
“…All, except two, studies investigated school-aged asthmatic and/or symptomatic children, while the remaining two considered infants and toddlers (Andersen et al 2008b;Coneus & Spiess, 2012). Most of the studies observed positive associations between short-term exposure to NO 2 (or nitrogen oxides) for different lags and respiratory symptoms, such as coughing and wheezing (O'Connor et al, 2008;Escamilla-Nuñez et al, 2008;Andersen et al, 2008b), as well as for exhaled nitric oxide (Sarnat et al, 2012) and also for pulmonary function decrease (O'Connor et al, 2008;Liu et al, 2009;Castro et al, 2009;Dales et al 2009;Min et al, 2008;Yamazaki et al, 2011;Ma et al, 2008) in children, although not all of them were statistically significant (Dales et al, 2009). One article reported numerical data only for PM (Min et al, 2008).…”
Section: Panel Studiesmentioning
confidence: 99%
“…A PubMed search identified 11 new articles: 6 from the Americas (Sarnat et al, 2012;O'Connor et al, 2008;Escamilla-Nuñez et al, 2008;Liu et al, 2009;Castro et al, 2009;Dales et al, 2009), 2 from Europe (Andersen et al, 2008b;Coneus & Spiess, 2012), and 3 from Asia (Min et al, 2008;Yamazaki et al, 2011;Ma et al, 2008). All, except two, studies investigated school-aged asthmatic and/or symptomatic children, while the remaining two considered infants and toddlers (Andersen et al 2008b;Coneus & Spiess, 2012).…”
Section: Panel Studiesmentioning
confidence: 99%
“…Additionally, Japanese epidemiological studies have shown associations between air pollutants and asthma prevalence [15][16][17][18]. Yamazaki et al, [19,20] found that the odds ratio (OR) in warmer months per 10 ppb increment in 24-hr mean concentration of surface ozone was 1.25 (95% Confidence Interval (CI): 0.87-1.82), and the association between ozone concentrations and asthma admissions for the preschool age group (2-5 years) was stronger than the age group of 6-14 years. Also rice crop, which is the main crop in Japan, is likely to be affected by surface ozone as it can be estimated easily based on AOT40 index (accumulated exposure over a threshold of 40 ppb calculated for three months during the growing season) [7].…”
Section: Introductionmentioning
confidence: 99%